Mortality by Parasitization in the Association between Diachasmimorpha tryoni (Hymenoptera: Braconidae) and Ceratitis capitata (Diptera: Tephritidae) under Field-Cage Conditions - Albornoz Medina, Patricia (2014)
Ceratitis capitata (Wiedemann) is one of the major pests currently affecting world fruit production. In Argentina?s northern Citrus-producing regions, C. capitata is actively multiplying in large exotic host fruits, such as Citrus paradisi Macfadyen (grapefruit), Citrus aurantium L. (sour orange) and Citrus sinensis L. (Osbeck) (sweet orange). Faced with this situation, the use of parasitoids as biocontrol agents is currently receiving renewed attention as a new biological tool for controlling pestiferous fruit flies within the Argentinean National Fruit Fly Control and Eradication Program (ProCEM). Consequently, a viable approach to controlling C. capitata involves the use of exotic parasitoids such as Diachasmimorpha tryoni (Cameron). In this study, the effectiveness of D. tryoni females to find and successfully parasitize C. capitata larvae infesting all Citrus species mentioned earlier was assessed. Parasitoids were allowed to forage for 8 h on grapefruits and oranges artificially infested with laboratory-reared C. capitata larvae under natural environmental conditions (field cage). Parasitoid emergence, parasitism, overall effectiveness, and sex ratio of parasitoid offspring were estimated as response variables. The higher effectiveness of D. tryoni females recorded from C. sinensis would be mainly a result of both increased host density per unit of fruit surface area and fruit physical features. The study provides evidence that D. tryoni contributed to C. capitata mortality in all Citrus species assessed. However, the mortality values recorded from C. sinensis, C. aurantium, and C. paradisi did not exceed 10%, 1.5%, and 1.7%, respectively. Nonetheless, D. tryoni might be selected to forage under both high and low host density conditions.